PENGARUH HIGH PERFORMANCE WORK PRACTICE (HPWP) TERHADAP JOB SATISFACTION DI RS XYZ MAGELANG - Deandra Michella; Yohana F. Cahya P. Meilani (FEB Universitas Sam Ratulangi Manado, 2023)
Globalization and evolution of technology is leading industries and organization to grow, including the health sector. The vast technological evolution, together with rapid development of infrastructure will not be optimum if it is not supported by reliable Human Resources. This study aimed to determine the effect of compensation, participation and training on job satisfaction. The data for this study is collected using an online questionnaire to 87 health workers at XYZ Hospital, Magelang City. The analysis was conducted using statistical analysis calculation using SmartPLS Software version 4.0. The results obtained from this study are that all variables, which is participation, training and compensation, has a positive impact on job satisfaction at XYZ Hospital, Magelang City.